Identifying important factors that influence job satisfaction among employees in Iskandar Regional Development Authority (IRDA) / Hajar Aseken Moktar - Moktar, Hajar Aseken (Faculty of Business and Management, 2009)
Job satisfaction is generally recognized as a multifaceted construct that includes employee feelings about a variety of both intrinsic and extrinsic job elements. It encompasses specific aspects of satisfaction related to pay, benefits, promotion, work conditions, supervision, organizational practices and relationships with co-workers (Misener et al., 1996). This study try to identify the major factors that will contributes job satisfaction among employees in Iskandar Malaysia. According to this research paper, the researcher will investigate the attitude towards workgroup, attitude toward management, monetary benefits and working condition will influence in job satisfaction within employees of IRDA.